A novel 6-axis hybrid additive-subtractive manufacturing process: Design and case studies. (June 2018) - Li, Lin; Haghighi, Azadeh; Yang, Yiran
Abstract: Additive manufacturing has been employed in numerous areas owing to its advantages of fabricating complex geometries and creating less material waste. Nevertheless, parts manufactured by additive manufacturing processes tend to have poor surface quality and low dimensional accuracy. To overcome the limitations of additive manufacturing technologies, the favorable capabilities of subtractive manufacturing, i.e., high surface quality, can be integrated to form a hybrid process. A novel 6-axis hybrid additive-subtractive manufacturing process is proposed and developed in this paper. The hybrid process is realized using a six degrees of freedom (DOF) robot arm, equipped with multiple changeable heads and an integrated manufacturing platform. Based on the obtained results from different case studies, the hybrid additive-subtractive process has shown to have potentials in reducing production time, fabricating parts with better surface quality by removing the staircase error, manufacturing high quality freeform surfaces through the dynamic adjustment of tool axis direction, and eliminating the need for support structure because of the 6-DOF flexibility.